Gastroprotective and microbiome-modulating effects of ubiquinol in rats with radiation-induced enteropathy - Walaa A. Eraqi; Walaa A. El-Sabbagh; Ramy K. Aziz; Mostafa S. Elshahed; Noha H. Youssef; Nora M. Elkenawy (Animal Microbiome, 2024)
Abstract Radiation enteritis is a frequently encountered issue for patients receiving radiotherapy and has a significant impact on cancer patients' quality of life. The gut microbiota plays a pivotal role in intestinal function, yet the impact of irradiation on gut microorganisms is not fully understood. This study explores the gastroprotective effect and gut microbiome-modulating potential of ubiquinol (Ubq), the reduced form of the powerful antioxidant CoQ-10. For this purpose, male albino rats were randomly assigned to four groups: Control, IRR (acute 7 Gy γ-radiation), Ubq_Post (Ubq for 7 days post-irradiation), and Ubq_Pre/Post (Ubq for 7 days pre and 7 days post-irradiation). The fecal microbiomes of all groups were profiled by 16S rRNA amplicon sequencing followed by bioinformatics and statistical analysis. Histopathological examination of intestinal tissue indicated severe damage in the irradiated group, which was mitigated by ubiquinol with enhanced regeneration, goblet cells, and intestinal alkaline phosphatase expression. Compared to the irradiated group, the Ubq-treated groups had a significant recovery of intestinal interleukin-1β, caspase-3, nitric oxide metabolites, and thio-barbituric reactive substances to near-healthy levels. Ubq_Pre/Post group displayed elevated peroxisome proliferator-activated receptor (PPAR-γ) level, suggesting heightened benefits. Serum insulin reduction in irradiated rats improved post-Ubq treatment, with a possible anti-inflammatory effect on the pancreatic tissue. Fecal microbiota profiling revealed a dysbiosis state with a reduction of bacterial diversity post-irradiation, which was re-modulated in the Ubq treated groups to profiles that are indistinguishable from the control group. These findings underscore Ubq's gastroprotective effects against radiation-induced enteritis and its potential in restoring the gut microbiota’s diversity and balance.